Inpatient treatment to online aftercare: E-mailing themes as a function of therapeutic outcomes - Wolf, Markus; Chung, Cindy K.; Kordy, Hans (Psychotherapy research, 2010)
The authors applied the meaning extraction method (MEM) to 4,241 e-mails written by 297 participants of an email-based aftercare program following inpatient psychotherapy. Principal-components analysis of the most frequently used nouns in the e-mails yielded nine components: life decisions and coping, relationship conflict, psychological and physical symptoms, family of origin, social and leisure activities, present family and household, treatment, exercise and diet, and work. Relative to men, women focused more on symptoms, exercise and diet, and family of origin, but less on work. Older participants were more likely to e-mail about their present family. Younger participants were more likely to e-mail about their family of origin and exercise and diet. Patients who showed no therapeutic gains during their prior treatment wrote more about symptoms than patients who had improved. The potentials and limitations of the MEM for the analysis of therapy corpora are discussed.